42 'Choice' and 'autonomy' for older people living with advanced frailty and their informal carers during hospital discharge. (30th January 2023) - McKean, Emily; Butler, Claire; Wilson, Patricia
Abstract : Introduction: There is a global theme of discharging ageing patients 'quicker and sicker, ' with the average length of admission decreasing (Lilleheie et al, 2019). Hospital admissions can increase in the last 3 months before death, with most of those having three or more emergency admissions being over 70 years old (Public Health England, 2020). Previous studies looking at frailty, end-of-life and hospital discharge are few. Aims: To explore the experiences of those involved in the discharge from community hospital of an older person living with frailty who is nearing the end-of-life. This included the patient, their informal carer(s), community hospital staff and health and social care staff in the community. Methods: A constructivist grounded theory methodology was used, and semi-structured interviews were conducted with 57 participants. Results: It has been discussed internationally how older people living with frailty are a disadvantaged group (WHO, 2021). This study found informal carers further disadvantaged, particularly when overwhelmed by the power of the 'drive to discharge' and set adrift by lack of resources in the community. Choices made by patients are based on many different factors that the drive to discharge may not allow for or anticipate (Gott et al, 2004). Home may be the preferred option for the patient but seem utterly overwhelming to the informal carer. Conclusions: The 'drive to discharge' causes a burden to the informal carer, which is exacerbated by a focus on patient-centeredness rather than the patient/carer intersection. Impact: This piece of work has significant importance for both older people living with frailty who are at the end of life but also their informal carers. It highlights causes of inequity and injustice during the discharge process at the end of life, and suggests how policy and practice could use relational ethics to improve outcomes and experiences through care planning and carer support. References: Gott M, Seymour J, Bellamy G, Clark D, Ahmedzai S. Older people's views about home as a place of care at the end of life. Palliative Medicine 2004;18 (5):460–467. Lilleheie I, Debesay J, Bye A, Bergland A. Experiences of elderly patients regarding participation in their hospital discharge: a qualitative metasummary. BMJ Open 2019;3 ;9(11). Public Health England. (2020). Emergency admissions in the 3 months before death. Available online: https://www.gov.uk/government/publications/emergency-admissions-in-the-3-months-before-death/emergency-admissions-in-the-3-months-before-death Wold Health Organisation. (2021). Ageism is a global challenge: UN. Available online at: https://www.who.int/news/item/18-03-2021-ageism-is-a-global-challenge-un